Does intermittent nutrition enterally normalise hormonal and metabolic responses to feeding in critically ill adults? A protocol for the DINE-Normal proof-of-concept randomised parallel-group study - Paul White; Matt Thomas; Javier T Gonzalez; Aravind V Ramesh; Anthony E Pickering; Danielle Milne; Borislava Borislavova; Clodagh Emer Beattie; Harry A Smith; Michael Ambler; Kati Hayes; James A Betts (BMJ Open)
Introduction Over half of patients who spend >48 hours in the intensive care unit (ICU) are fed via a nasogastric (NG) tube. Current guidance recommends continuous delivery of feed throughout the day and night. Emerging evidence from healthy human studies shows that NG feeding in an intermittent pattern (rather than continuous) promotes phasic hormonal, digestive and metabolic responses that are important for effective nutrition. It is not yet known whether this will translate to the critically ill population. Here, we present the protocol for a proof-of-concept study comparing diurnal intermittent vs continuous feeding on hormonal and metabolic outcomes for patients in the ICU.Methods and analysis The study is a single-centre, prospective, randomised, open-label trial comparing intermittent enteral nutrition with the current standard practice of continuous enteral feeding. It aims to recruit participants (n=30) needing enteral nutrition via an NG tube for >24 hours who will be randomised to a diurnal intermittent or a continuous feeding regimen with equivalent nutritional value. The primary outcome is peak plasma insulin/c-peptide within 3 hours of delivering the morning intermittent feed on the second study day, compared with that seen in the continuous feed delivery group at the same time point. Secondary outcomes include feasibility, tolerability, efficacy and metabolic/hormonal profiles.Ethics and dissemination We obtained ethical approval from the Wales Research Ethics Committee 3 prior to data collection (reference 23/WA/0297). We will publish the results of this study in an open-access peer-reviewed journal.Trial registration number NCT06115044.